IMPROVING THE PERFORMANCE OF EDUCATION TEACHERS IN THE MERDEKA CURRICULUM: THE ROLE OF LEADERSHIP, SCHOOL CLIMATE, AND JOB SATISFACTION - Damanik, Suryadi; Mesnan, Mesnan; Mudjisusatyo, Yuniarto; Damanik, Saipul Ambri; Puspita, Syarifah (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
The implementation of the Merdeka Curriculum in Indonesia demands high teacher performance, especially for physical education (PE) teachers, who must adopt differentiated, student-centered learning approaches. This study aims to analyze the effects of principal leadership, school climate, and teacher job satisfaction on the performance of PE teachers in implementing the curriculum. A quantitative ex post facto design was employed, involving 30 principals and 30 teachers, with data collected via structured questionnaires and analyzed using path analysis. The results show that principal leadership contributed 36.6%, school climate 42.3%, and job satisfaction 50.5% to teacher performance. These findings highlight the crucial role of transformational leadership, a positive school environment, and job satisfaction in curriculum success. The novelty of this study lies in its focus on PE teachers—an area underexplored in Merdeka Curriculum research. The study provides practical implications for educational policymakers and school leaders to enhance curriculum implementation through leadership development and the cultivation of supportive school environments. Ultimately, the findings emphasize that optimizing PE teacher performance requires a comprehensive approach that integrates organizational, emotional, and instructional supports.